High voltage and electrical insulation engineering - Arora, Ravindra; Mosch, Wolfgang (Hoboken, NJ : J. Wiley, 2011)
'The book is written for students as well as for teachers and researchers in the field of High Voltage and Insulation Engineering. It is based on the advance level courses conducted at TU Dresden, Germany and Indian Institute of Technology Kanpur, India. The book has a novel approach describing the fundamental concept of field dependent behavior of dielectrics subjected to high voltage. There is no other book in the field of high voltage engineering following this new approach in describing the behavior of dielectrics. The contents begin with the description of fundamental terminology in the subject of high voltage engineering. It is followed by the classification of electric fields and the techniques of field estimation. Performance of gaseous, liquid and solid dielectrics under different field conditions is described in the subsequent chapters. Separate chapters on vacuum as insulation and the lightning phenomenon are included'--
Includes bibliographical references and index.
Keywords: Electric insulators and insulation; Electric power distribution -- High tension; Electric cables -- Insulation